An intelligent decision-making system for flood monitoring from space - Yuhaniz, Siti; Vladimirova, Tanya; Gleason, Scott (IEEE, 2007)
This paper presents the results of a feasibility study on intelligent image processing and decision-making for flood monitoring on board satellites. The ability to detect temporal changes in images is one of the most important functions in intelligent image processing systems for hazard and disaster monitoring applications. An automatic change detection system is proposed, the purpose of which is to monitor particular areas on Earth and give warnings to the authorities if any flooding events are detected. A novel solution to flood detection based on combined use of optical multispectral imagery and GPS reflectometry data is introduced. A fuzzy inference engine is used in the decision-making process, which generates control signals to other subsystems on board the satellite.